Socioeconomic status and internalizing–externalizing behaviours as predictors of student subjective well-being among adolescents - Ghina Aliya Mufidah; Asri Mutiara Putri; Prida Harkina (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: High school students in coastal communities may experience academic, psychological, and socioeconomic challenges associated with their quality of school life. Purpose: To examine the simultaneous and individual associations of parental socioeconomic status and internalizing–externalizing behaviours with student subjective well-being. Method: This quantitative cross-sectional correlational study involved 248 Grade X and XI students at Senior High School 1 Padang Cermin, Lampung, recruited through quota sampling. Data were collected using the Student Subjective Well-Being Questionnaire (SSWQ), a socioeconomic status index adapted from the Kuppuswamy scale, and the Youth Internalizing and Externalizing Problems Screener (YIEPS). Results: The overall regression model was statistically significant, indicating that parental socioeconomic status and internalizing externalizing behaviours were jointly associated with student subjective well-being. Conclusion: Internalizing externalizing behaviours were more strongly associated with lower student subjective well-being than parental socioeconomic status in this sample. The limited variation in socioeconomic status may partly explain its nonsignificant association. These findings suggest that school-based psychological support and early behavioural interventions may help improve students' subjective well-being. Keywords: Adolescents; Internalizing and Externalizing Behaviours; Socioeconomic Status; Student Subjective Well-Being.